Emotional intelligence among nursing student in Universiti Malaysia Sarawak - Farrah Nadia, Fouzi (Faculty of Medicine & Health Sciences, 2008)
Emotional Intelligence (EI) is the ability to recognize our own feelings and those of others, for motivating ourselves and others. It is a new knowledge and skills for the nurses that should be cultivated in order to improve the nurses' quality work. The main aims of this study are to identify the level of awareness and the level of EI among nursing students in Univesiti Malaysia Sarawak (UNIMAS). This study used a quantitative method and 109 nursing students were selected by convenience sampling.